The Effect of Capital Structure, Liquidity and Company Size on Profitability - Muzaki, Rifki Amrul; Damayanti, Fera; Espa, Vitryan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The Indonesian government has announced a policy regarding the plan to move the capital city to the National Capital, which is expected to affect the profitability of companies in the property and real estate sector. This study aims to determine and analyze the effect of capital structure, liquidity, and company size on the profitability of property and real estate companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Looking through a quantitative approach, data is processed and analyzed using statistical methods. The results of the study indicate that company size has a positive effect while the debt-to-equity ratio (DER) and current ratio (CR) have a negative effect on company profitability. Investors should consider paying attention to the balance between the use of debt, liquidity, and efficiency of company size when evaluating investment prospects. Future research can expand the scope and variables to provide a more comprehensive understanding of the factors that influence profitability in a company.